Addenda to the insects found in birds’ nests from the Neotropical Region and Neotropical immigrants in the Nearctic Region, with a discussion of the probable transmission mechanism of Ornithocoris toledoi (Hemiptera: Cimicidae) - Iorio, Osvaldo Di; Turienzo, Paola (Zootaxa, 2012)
The present work adds some records to the insect fauna in birds’ nests from the Neotropical Region and Neotropical im-migrants in the Nearctic Region. Unpublished records of Triatominae (Hemiptera: Reduviidae) prior to 2005 are includedhere, especially the localities of some specimens from the collection of Antonio Martínez. According to new data recentlypublished, the probable transmission mechanism of Ornithocoris toledoi (Hemiptera: Cimicidae) is presented here and discussed.